Behaviour of Oil Palm Shell Reinforced Concrete Beams Added With Kenaf Fibres - Sharifah Maszura, Syed Mohsin; Sayid Javid, Azimi; Abdoullah, Namdar (2014)
The present article reports the findings of a study into the behaviour of oil palm shell reinforced concrete (OPSRC) beams with the addition of kenaf fibres. This work aims at examining the potential of kenaf fibres to improve the strength and ductility of the OPSRC beams as well as observing its potential in serving as part of shear reinforcement in the beams. Two different arrangements of the shear links in OPSRC beams with a selection of kenaf fibres content (10kg/rn3 and 20kg/rn3 , respectively) were tested under monotonic loading. The results show that the addition of kenaf fibres enhances the load carrying capacity, ductility apart from altering the failure mode of the beams from brittle shear mode to flexural ductile mode. Furthermore, the study shows that kenaf fibres are compatible with OPSRC with desirable results.